2022
DOI: 10.5194/amt-15-6739-2022
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of atmospheric CFC-11 and CFC-12 from high-resolution FTIR observations at Hefei and comparisons with other independent datasets

Abstract: Abstract. Synthetic halogenated organic chlorofluorocarbons (CFCs) play an important role in stratospheric ozone depletion and contribute significantly to the greenhouse effect. In this work, the mid-infrared solar spectra measured by ground-based high-resolution Fourier transform infrared spectroscopy (FTIR) were used to retrieve atmospheric CFC-11 (CCl3F) and CFC-12 (CCl2F2) at Hefei, China. The CFC-11 columns observed from January 2017 to December 2020 and CFC-12 columns from September 2015 to December 2020… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…Chirkov et al (2016) found that the HCFC-22 minimum value in the northern hemisphere during the spring may be related to the invasion of the stratospheric air lacking HCFC-22 at the end of the polar winter and during the breakdown of the polar vortex based on MIPAS satellite data [51]. Other tropospheric sources, such as CFCs, also reach the minimum in the spring at the Hefei station [52].…”
Section: Annual Trend and Seasonal Cyclementioning
confidence: 99%
“…Chirkov et al (2016) found that the HCFC-22 minimum value in the northern hemisphere during the spring may be related to the invasion of the stratospheric air lacking HCFC-22 at the end of the polar winter and during the breakdown of the polar vortex based on MIPAS satellite data [51]. Other tropospheric sources, such as CFCs, also reach the minimum in the spring at the Hefei station [52].…”
Section: Annual Trend and Seasonal Cyclementioning
confidence: 99%
“…As is shown in Figure 7, the typical DOFs for H 2 O over Hefei are about 2.53. This indicates that the retrieved profile can be separated into two independent partial columns, because the criterion for separating columns into separate layers is that the column DOFs of gases is greater than 1.0 [22,40,41]. We calculate the ground layer H…”
Section: The Retrieval Strategy Of Mir H 2 O Columnmentioning
confidence: 99%